A new temporal control approach for SCAO systems. (3rd December 2019) - Pöttinger, Markus; Ramlau, Ronny; Auzinger, Günter
Abstract: Adaptive optics (AO) systems for ground-based telescopes use deformable mirrors to physically correct wavefront distortions induced by atmospheric turbulence. Due to time delays caused by different parts of the AO system, the process of turbulence correction becomes even more difficult since the earth's atmosphere changes continuously. In this paper we propose a new temporal control approach for the computation of optimal mirror configurations based on the solution of a sequence of inverse problems for the wavefront sensor operator. Our mathematical formulation of the underlying problem allows the incorporation of computationally efficient wavefront reconstruction methods and a wavefront prediction step. Based on the frozen flow assumption, the prediction of a future wavefront relies on a suitable shift of the reconstructed wavefront. The performance of our temporal control algorithm is demonstrated in the context of a single conjugate adaptive optics system on a 37 meter telescope using a Shack–Hartmann wavefront sensor. Numerical results of the proposed control method are provided using OCTOPUS, the official end-to-end simulation tool of the European Southern Observatory.